Cyberspace as a national security issue in Malaysia - Ainaa Nadzirah binti Malek Farok (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study explains the linkages between cyberspace and national security of Malaysia. It also discusses the views of government personnel as well as those from private agencies about the relationship between cyberspace and national security of the country. The thesis examines the nature of threats to cyberspace in public and private sectors in Malaysia, and also analyses the policies adopted by the Malaysian government to deal with cyber threats in Malaysia. The research uses both primary and secondary sources. It uses data collected from online interviews conducted with a number of personnel working in public and private agencies in Malaysia. Data were also collected from such primary sources as official reports, publications and various documents on the subject published by CyberSecurity Malaysia, Bank Negara Malaysia, and the Malaysian Communications and Multimedia Commission.These primary sources were supplemented by various newspaper reports, books, magazines, and scholarly journals on the subject matter of this thesis. This study has found a clear relationship between Malaysia's cyberspace and the country's national security. The major threats to Malaysia's national security emanating from cyberspace are mostly centred on cyber-crimes. However, the thesis has also discovered that there is a lack of public awareness about cyber-crimes and other forms of threats to cyberspace in Malaysia. It is only through the adoption of strong policies and measures by the government that cyber threats and cyber-crimes can be dealt with. It is recommended that more measures should be undertaken by both the government and the private sectors to undertake technological and social research on the subject matter. In addition, government policies need to be looked at from time to time and if necessary, adopt new policies to keep them at pace with new technological innovations. The cooperation between various local and international agencies must be developed further in order to make sure that Malaysia's cyberspace is safe and remains well-protected, and thus making sure that Malaysia's cyber-security remains secured.